Addressing Constraints to South Africa’s Agriculture Inclusiveness - Sihlobo, Wandile; Qobo, Mzukisi (Southern Centre for Inequality Studies (SCIS), 2021)
South Africa’s agriculture remains dualistic, with large scale commercial farmers who are predominately white and small-scale and subsistence farmers that are mainly black. These disparities in fortunes result from the long history of segregation policies and apartheid. The efforts to build an inclusive agricultural sector through the upliftment of black farmers by the new democratic government since 1994 have failed. As such, black farmers in South Africa still constitute between 5 and 10 per cent of the overall commercial production. We explore the constraints to inclusive growth drive in the agricultural and agribusiness sector and offer recommendations for improvement. These include a need for increased efficiency at the local government for ensuring service delivery to farming towns, blended finance instruments for funding farmer development, and the prioritization of private-public-partnership approaches for farmer development and land reform projects. We frame the interventions for the post-COVID-19 dispensation, focusing on the potential role of agriculture in fostering inclusion and supporting rural economies and employment.
Keywords: Black Economic Empowerment; South Africa’s agriculture; Commercial farmers; Subsistence farmers; Segregation policies; Apartheid; Private-public-partnership; Commercial production; Agricultural sector